PENYULUHAN MASTITIS SUBKLINIS PADA SAPI PERAH DI DESA MEKAR BAKTI KECAMATAN PAMULIHAN KABUPATEN SUMEDANG JAWA BARAT - SARASATI WINDRIA (Dharmakarya, 2018)
Subclinical mastitis is an inflammation of the udder that often attacks livestock, especially milk-producing livestock. The impact of the loss of subclinical mastitis is quite large, including a dramatic decrease in the quantity and quality of milk, but no pathological changes in cattle have been found. Mekar Bakti Village, located in Pamulihan Subdistrict, Sumedang Regency, West Java, is one of the villages that is the center for producing milk in the Sumedang Region. The high incidence of subclinical mastitis encourages counseling regarding subclinical mastitis. Promotion activities were carried out by presenting material about subclinical mastitis with lecture techniques (power point slides), videos and discussion. In addition, efforts to increase livestock yields were carried out by giving information on the technique of making "Liquid Organic Cattle Fertilizer Intensification" (PITSA OC) and training in making pasteurized cow milk. This series of counseling activities is an effort to reduce the incidence of subclinical mastitis through increasing community knowledge.